Media Digital dan Radikalisme Penekanan pada Bias Pemberitaan Media Mainstream - Aminah, Siti; Rafiq Al Raruq, Muhammad; Asyfa, Nuraida (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The objective of this research is to determine the extent to which mainstream news influences perceptions and the spread of radicalism in society, especially through online platforms. It covers several aspects: 1. Analyzing the impact of digital media on the spread of radicalism aims to understand how digital media affects the dissemination of extreme views and radicalism in society. 2. Identifying factors causing bias in mainstream media reporting to identify the factors that contribute to bias in mainstream media related to radicalism issues. 3. Investigating the influence of bias in reporting on public opinion explores how bias in mainstream media can affect public opinion and perceptions of groups related to radicalism .4. Seeking solutions or recommendations to address bias in reporting and radicalism identifies problems and seeks policy solutions or recommendations that can reduce bias in mainstream media reporting and address the spread of radicalism through digital media. 5. Contributing to understanding how digital and mainstream media play roles in the dissemination of radical information and enhancing public criticism of received information. 6. Encouraging changes in media behavior and practices in presenting news to be more accurate, balanced, and responsible in addressing issues of radicalism. This study uses content analysis to examine how mainstream media report on issues related to radicalism. Findings indicate that mainstream media tends to reinforce stereotypes and narratives that worsen perceptions of certain groups, which can increase societal polarization and support radical agendas.The conclusions is the emphasis on bias in mainstream media reporting in the context of radicalism underscores the importance of greater media criticism and the need for regulation that considers the social impact of information conveyed by digital media. The implications of this research highlight the importance of prudent handling of digital media to prevent the spread of radicalism and promote healthy and inclusive dialogue in society.